EFISIENSI DAN PENDAPATAN PETANI PETERNAK KAMBING RAKYAT DI KELURAHAN POBOYA KECAMATAN PALU TIMUR KOTA PALU - Jauhar, Andi (AgriSains, 2013)
This research aim to know (1) the efficient use of production factor of goat livestock at Poboya village, Palu Timur subdistrict, Palu city (2)the level of income obtained by goat breeder at Poboya village, Palu Timur subdistric, Palu City. Research method used was a survey method and sample collection through census. Results of research show (1) the use of size cage factor, kids, feed, and were not efficient in production of goat livestock at Poboya Village, Palu Timur subdistrict, Palu city, so that the four production factors require to be added to reach the maximal goat livestock production (2) level of income obtained by breeder of goat at Poboya village, Palu Timur subdistrict, Palu City was in average ofRp 2.558.345,18/17 head/year, or Rp. 213.195,43 for 17 heads/month. Keywords : efficiency, income, people goat.